Caregiver Perceptions and Motivation for Disclosing or Concealing the Diagnosis of HIV Infection to Children Receiving HIV Care in Mbarara, Uganda: A Qualitative Study - Kiwanuka, Julius; Mulogo, Edgar Mugema; Haberer, Jessica E (My University, 2014)
Background: Disclosure of the diagnosis of HIV to HIV-infected children is challenging for caregivers. Despite current recommendations, data suggest that levels of disclosure of HIV status to HIV-infected children receiving care in resource limited settings are very low. Few studies describe the disclosure process for children in these settings, particularly the motivators, antecedent goals, and immediate outcomes of disclosure to HIV-infected children. This study examined caregivers’ perception of the disclosure concept prior to disclosure, their motivation towards or away from disclosure, and their short- and long-term intentions for disclosure to their HIV-infected children. Methods: In-depth interviews were conducted with primary caregivers of 40 HIV-infected children (ages 5–15 years) who were receiving HIV care but did not know their HIV status. Results: Caregivers of HIV-infected children mainly perceived disclosure as a single event rather than a process of gradual delivery of information about the child’s illness. They viewed disclosure as potentially beneficial both to children and themselves, as well as an opportunity to explain the parents’ role in the transmission of HIV to the children. Caregivers desired to personally conduct the disclosure; however, most reported being over-whelmed with fear of negative outcomes and revealed a lack of self-efficacy towards managing the disclosure process. Consequently, most cope by deception to avoid or delay disclosure until they perceive their own readiness to disclose. Conclusions: Interventions for HIV disclosure should consider that caregivers may desire to be directly responsible for disclosure to children under their care. They, however, need to be empowered with practical skills to recognize opportunities to initiate the disclosure process early, as well as supported to manage it in a phased, developmentally appropriate manner. The potential role for peer counselors in the disclosure process deserves further study.
Keywords: Caregiver; Perceptions and Motivation; Disclosing or Concealing; Diagnosis; HIV Infection; HIV Care; Mbarara; Uganda